Potassium Bromate Concentration Measurement in Local Bread Types from Various Bakeries in Zawia, Libya - Abtisam S. Aljarmi; Najah Y. Baroud; Mabrouka M. Hamzah; Rania A. Alrwesse (African Journal of Advanced Pure and Applied Sciences, 2024)
Bread is widely consumed in Libya, primarily for breakfast, dinner, and school meals, by people from all socioeconomic backgrounds. In the banking sector globally, potassium bromates to their blends. This research aims to determine the degree of compliance with the prohibition fourteen years later and to evaluate the safety of bread by measuring residual potassium bromate with a fast and accurate technique (spectrophotometric technique), from various bakeries in Zawiya, Libya, twenty-nine distinct bread samples were chosen randomly. The reducing-oxidant reaction of bromate and promethazine in an acidic media is the basis for this technique. At 515 nm, the reddish-pink product that was formed had the highest absorption. According to the results, every bread sample that was examined contained potassium bromide. In the bread samples, the amount of bromated varied between 9 and 60 mg per kg. The French bread sample showed the lowest level, while the Fino bread sample showed the highest level. This investigation shows that all four varieties of bread samples have potassium bromate levels above WHO guidelines.